The mission of the Portuguese Augustinians to Persia and beyond (1602-1747) - Flannery, John M. (Studies in Christian Mission, 2013)
In The Mission of the Portuguese Augustinians to Persia and Beyond (1602-1747), John M. Flannery describes the establishment and activities of the Portuguese Augustinian mission in Persia. Hopes of converting the Safavid ruler of the Shi'a Muslim state would come to naught, as would the attempts of Shah 'Abbas I to use the services of the missionaries, as representatives of the Spanish Habsburgs, to forge an anti-Ottoman alliance with the papacy and the Christian rulers of Europe. Prevented from converting Muslims, the Augustinians turned their attention to Armenian and Syriac Christians in Isfahan, later also establishing new missions among Christians in Georgia and the Mandaeans of the Basra region, all of which are described herein. The history of the Augustinian Order is generally under-represented by contrast with other Orders, and this study breaks new ground in existing scholarship.